Deformed Entropic and Information Inequalities for X-States of Two-Qubit and Single Qudit States - V. I. Man’ko; L. A. Markovich (Advances in Mathematical Physics)
The q-deformed entropies of quantum and classical systems are discussed. Standard and q-deformed entropic inequalities for X-states of the two-qubit system and the state of single qudit with j=3/2 are presented.